Detection of Klebsiella spp. Causing Subclinical Mastitis in Sows on Farms in Puhu Village, Gianyar, Bali - Ni Putu Deana Kanaya Sahrani; I Ketut Suada; Ni Nyoman Werdi Susari; Romy Muhammad Dary Mufa (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Subclinical mastitis is a disease that quite often affects sows during lactation without any apparent clinical symptoms, one of which is caused by Klebsiella Spp. The purpose of this study was to determine the quality of pig milk and whether Klebsiella spp. was detected in the pig milk. Thirty-four samples were tested using the California Mastitis Test (CMT) method, and samples positive for subclinical mastitis were further tested using MacConkey media. Additional tests were conducted, including the TSIA biochemical test and microscopic examinations of the growing bacterial isolates, to confirm the bacterial identity. The results of this study showed that 29 out of 34 positive samples had subclinical mastitis with different levels of severity. According to the laboratory results, the presence of Klebsiella spp (85%) bacteria was identified. The results of this study indicate that subclinical mastitis caused by Klebsiella spp remains a significant threat in pig farms in Puhu Village, Payangan Subdistrict, Gianyar Regency, particularly when cage sanitation and management are not optimal. Early detection and improved husbandry systems are needed to prevent similar incidents.